(untitled) (Indian Journal of Public Health Research & Development, 2020)
Aim: To evaluate the government health expenditure and its impact on health of the population in Indian states. Methodology: This review paper was done by computing the data from the National health profile (2018, 2019), public health expenditure (national health accounts) and Health indicators (NITI AAYOG). Detailed Demand for Grants of the state governments and the National Rural/Urban Health Mission data have been adopted for the study. Exploratory data analysis and benefit incidence analysis have been administered to estimate the utilization, OOPE (Out of pocket expenditure) and degree of equity in the states. Results: An increase in the utilization of health care facilities for treatment was an important objective of any health care system. Especially, the increase in the utilization of public facilities will help to achieve health goals by reducing out-of-pocket expenditure. Chattisgarh had recorded the highest crude death Rate of 7.4% whereas Jammu and Kashmir recorded the lowest crude death rate of 5.0%. Kerala recorded the highest life expectancy at a birth rate of 74.9% whereas Assam recorded the lowest life expectancy at a birth rate of 63.9%. Conclusion: In the future, there is a need to design the schemes and implement safeguards so that health outcome risks can be minimized. These are also states, which have low health achievements and pull down the health indicators for the country. Achieving health goals in the country would require central transfers for the health sector to be exactly targeted at these states